Multi-omics analysis reveals Jianpi formula-derived bioactive peptide-YG-22 potentially inhibited colorectal cancer via regulating epigenetic reprogram and signal pathway regulation - Jun Wang; Jun Wang; Lijuan Zhu; Yuanyuan Li; Mingming Ding; Xiyu Wang; Bo Xiong; Hongyu Chen; Lisheng Chang; Wenli Chen; Bo Han; Jun Lu; et al. (Frontiers in Genetics)
IntroductionColorectal cancer (CRC) is a prevalent malignancy worldwide, often treated with chemotherapy despite its limitations, including adverse effects and resistance. The traditional Chinese medicine (TCM) Jianpi formula has been demonstrated to improve efficacy of chemotherapy, however the underlying mechanisms still need to be explored. In this study, we aim to screen bioactive peptides derived from the blood of CRC patients through peptidomics and explore the molecular mechanisms of the candidate peptides in the inhibition of CRC using multi-omics analysis.MethodsIn this study, we recruited 10 patients with CRC who had received either adjuvant chemotherapy or adjuvant chemotherapy combined with the traditional Chinese medicine Jianpi formula after surgery. We collected plasma samples at 2 cycles of adjuvant therapy and performed peptidomic analysis on these samples. The differentially bioactive peptides were screened using a model of HCT116 cells in vitro. To investigate the molecular mechanism underlying YG-22’s inhibition of the colorectal cancer cell line HCT116, we performed a multi-omics analysis, including transcriptome, metabolome, chromatin accessibility, H3K4Me3 histone methylation, and NF-κB binding site analyses.ResultsDifferential peptides were identified in plasma samples from patients treated with adjuvant chemotherapy combined with the Jianpi formula. Among these peptides, YG-22 exhibited the strongest cytotoxic effect on HCT116 cells, reducing cell viability in a dose- and time-dependent manner. Transcriptome analysis highlighted that YG-22 treatment in CRC modulates key pathways associated with lysosome-mediated degradation and apoptosis. Metabolomic profiling further indicated disruptions in tumor-supportive metabolic pathways. Chromatin accessibility and histone modification analyses suggested that YG-22 induces epigenetic reprogramming. Additionally, treatment with YG-22 resulted in significant changes in NF-κB binding and pathway activation.ConclusionsThis study demonstrates that combining chemotherapy with TCM Jianpi formula enriches the molecular landscape and generates bioactive peptides with strong antitumor activity. Furthermore, this study also lays the foundation for further development of peptide-based therapies and highlights the value of combining traditional and modern therapeutic strategies for CRC management.